Copper-Catalyzed Selective Synthesis of Highly Substituted Pyridones by the Reaction of Enaminones with Alkynes - Shao, Yushang; Yao, Wenjun; Liu, Jun; Zhu, Kai; Li, Yanzhong (Synthesis, 2012)
An efficient copper-catalyzed selective synthesis of highly functionalized pyridones by the reaction of enaminones with alkynes is reported. The reactions proceed to afford polysubstituted pyridone derivatives in good to high yields using CuI as the catalyst in MeCN under nitrogen.
Keywords: copper catalysis; pyridones; regioselective cyclization; enaminones; cascade reactions